Union wage effect: Evidence from Ghana - John Owusu-Afriyie; Priscilla Twumasi Baffour; William Baah-Boateng (Cogent Economics & Finance, 2023)
Consistent with Convention 87 of the International Labour Organization (ILO), Section 79 of the Labour Act, 2003 (Act 651) empowers every employee in an organization to either form or join a trade union of their choice for the promotion and protection of their economic and social interests. In spite of this legal provision, union coverage and density in Ghana have continually declined in recent years. The decline in union density and coverage is likely to decrease the collective bargaining strength of unions. It is against this background that our study seeks to examine the effect of unions' bargaining (proxied by union presence variable) on wages in Ghana. We employ the Heckman Selection Model and quantile regression technique to analyze data extracted from the sixth round of the Ghana Living Standards Survey (GLSS 6) and 2015 Ghana Labour Force Survey (GLFS 2015) respectively. The findings indicate that unions' bargaining effect on wages is positive. Furthermore, the study finds that the union wage premium is highest at the lowest point of the wage distribution (25th quantile) but lowest at the highest point of the wage distribution (75th quantile). Whilst the study acknowledges the importance of education in earnings determination, we recommend that low-wage employees in a non-union establishment should join a trade union in order to earn a living/decent wage.
Keywords: D02; J01; J08; J31; J51; 330; and Ghana; Collective Bargaining; Labour Act; Unions; Wages